2011
DOI: 10.1182/blood-2010-09-308775
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hematopoietic stem cell transplantation in chronic lymphocytic leukemia: results of European intergroup randomized trial comparing autografting versus observation

Abstract: We present results of a phase 3 randomized trial of autografting in chronic lymphocytic leukemia versus observation for responding patients after first-or secondline treatment. The primary objective was to demonstrate that autografting improves the 5-year event-free survival (EFS) from 30% to 50%. There were 223 enrolled patients, 72% men and 28% women, 83% after first and 17% after second-line treatment. Binet stages were progressive A 13%, B 67%, C 20%; at randomization, 59% were in complete remission, and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 34 publications
4
40
0
Order By: Relevance
“…Even though their common origin is still uncertain, [19][20][21] clinical, genetic and immunophenotypic similarities between B-CLL and mantle cell lymphoma (namely, presence in the peripheral blood of clonal B lymphocytes, absence of IGVH somatic mutations and expression of common antigens), as well as the very high durable remission rate obtained by our group in the latter patients upon high-dose chemotherapy regimens, 22,23 encouraged the use of this treatment modality in B-CLL patients. Previous reports 3,4,7,9 suggested the superiority of ASCT over conventional therapy in terms of EFS. However, those results are difficult to compare with ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though their common origin is still uncertain, [19][20][21] clinical, genetic and immunophenotypic similarities between B-CLL and mantle cell lymphoma (namely, presence in the peripheral blood of clonal B lymphocytes, absence of IGVH somatic mutations and expression of common antigens), as well as the very high durable remission rate obtained by our group in the latter patients upon high-dose chemotherapy regimens, 22,23 encouraged the use of this treatment modality in B-CLL patients. Previous reports 3,4,7,9 suggested the superiority of ASCT over conventional therapy in terms of EFS. However, those results are difficult to compare with ours.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, in spite of the large number of reports, 3,4 randomized trials comparing R-FC and autologous stem cell transplant (ASCT) are still lacking while there is recent evidence supporting the use of R-FC in the front-line setting. 5 Since ASCT appears to be a reasonably safe procedure, and ASCT trials performed so far are difficult to compare for differences in myeloablative regimens, use of MoAbs, graft purging and type of chemotherapy, [6][7][8][9] we started a multicenter, randomized, phase 3 trial comparing R-FC and highdose chemotherapy supported by ASCT in patients under 65 years of age, with stage B(II) or C B-CLL in 2005. The aim was to study the feasibility of early therapeutic intensification and compare its efficacy with the best therapeutic option available.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular disease detected by PCR was highly predictive of disease recurrence. Finally, Michallet et al 11 recently reported the EBMT experience in the first randomized trial of autografting vs observation for responding patients after first-or second-line treatment. First-and second-line induction treatments were left to the discretion of investigators and were heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 A German risk-matched retrospective comparison of auto-SCT vs conventional chemotherapy showed a survival benefit in auto-SCT patients, even in patients with unmutated IgVH. 9 Michallet et al 11 recently reported the EBMT experience in the first randomized trial of autografting vs observation for responding patients: inclusion criterion was patients after first-or second-line treatment; these treatments were left to the discretion of investigators and the trial population was restricted to those who had already achieved a CR, VGPR (very good PR) or nPR.…”
Section: Introductionmentioning
confidence: 99%
“…This therapy is not curative and subsequent clinical progression is inevitable (Provan et al, 1996;. The results of a phase 3 randomized European Group for Blood and Marrow Transplantation trial of autologous stem cell transplantation show the reduction of the risk of progression of CLL by more than 50%, but it does not have an effect on overall survival (Michallet et al, 2011), and it is particularly concerning the high incidence of myelodysplastic syndrome (9-12%) (Kharfan-Dabaja et al, 2007). Therefore, it is necessary to look for other solutions of treatment in this disease different from the chemotherapy and to move toward alternative non-chemotherapy-based treatment approaches.…”
Section: Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%